Cardiac Magnetic Resonance Identified the Fibrotic Lesion Associated with Syncope Attack Due to Complete Atrioventricular Block in a Patient with Hypertrophic Cardiomyopathy and Aortic Stenosis - Kawamura, Takayuki (Intern Med, 2019)
An 84-year-old man presented with syncope. Prior to admission, ambulatory electrocardiogram had demonstrated non-sustained ventricular tachycardia. Echocardiography showed severe aortic stenosis. He was also diagnosed with hypertrophic cardiomyopathy (HCM) by cardiac magnetic resonance (CMR) showing remarkable inhomogeneous left ventricular hypertrophy and extensive late gadolinium enhancement (LGE) in the lesions at the upper border and right-ventricular side of the basal-mid septal wall. Finally, he showed complete atrioventricular (AV) block followed by a long pause and syncope several times after admission. In this case with several possible causes of syncope, the CMR findings suggested a clue concerning the etiology of his syncope: complete AV block in HCM.